INFORMATION SUPPORT OF MANAGEMENT ACCOUNTING ACTIVITIES OF LOGISTICS ORGANIZATIONS - E. Yu. Knyazeva; O. S. Dyakonova (Вестник университета, 2019)
The article is devoted to topical issues of information support of management accounting of logistics organizations. It has been noted, that the basis of rational management of the logistics sector are information resources, which are formed by the movement, processing and structuring of data, necessary to improve the efficiency of the enterprise. Therefore, the collection and analysis of reliable information, that can influence management decisions, is a priority task to ensure economic processes in the enterprise. It has been proved, that the decision of problems of information support in activity of the logistic organization has to have complex character. The functional components of the information support of the logistics organization have been highlighted. Elements of information support of activity of the logistics organization have been listed. For the purpose of effective management, the study developed the basic principles of information management accounting activities of logistics organizations. The system of the main characteristics of the information component, through which the quality, reliability and completeness of the output flow of information is predetermined, has been adduced